Rediseño geométrico de la vía urbana: caso intersección de la Avenida Bolívar Madero Vargas con la Circunvalación Norte y Sur de la ciudad de Machala. - Vásquez Buele, Jessica Maribel (2015)
This work qualification aims, Geometrically Redesign urban roads: case intersection of Avenida Bolivar Madero Vargas with the northern ring road and south of the city of Machala, the study brings together all the positive aspects, as an acceptable view of the landscape, easy access and above all geometrically redesign it appropriately, according to research or studies conducted. TRAFFIC STUDY, GEOMETRICO REDESIGN: To achieve this purpose a suitable job as possible of what contains the following topics done In recent years, demand has grown road by increasing the number of motor vehicles, it can be said that the offer is well below the traffic demand. This has resulted in increases in congestion, delays, accidents, significantly higher than those considered acceptable. Urban intersections offer potential research avenues geometric redesign; the intersection of Avenida Bolivar Madero Vargas with the northern ring road and south is very important for the city of Machala, so it provides great benefits as it serves to address an important parish as Puerto Bolivar and other sectors, this route has a length of 0.47 km. It is easy to see that the people of this area have many reasons to require an improvement in the area with which this project arises based on the need for these. For the development of this project initially recognition site was conducted, and a comprehensive traffic study and it is also considered a survey which provides data on the characteristics and parameters needed for the redesign.